2021
DOI: 10.7759/cureus.17238
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Saudi Patients With Sickle Cell Disease: A Retrospective Multi-Center Study

Abstract: Background The prevalence of sickle cell disease (SCD) within Saudi Arabia is relatively high, with an estimated 145/10,000 cases. There is an urgent need for researching many aspects of the Coronavirus disease of 2019 (COVID-19) due to the widespread of the virus among SCD patients in Saudi Arabia. The aim of this study is to determine how COVID-19 affects SCD patients in order to reach the best strategy for their management protocols. Methods This is a retrospective chart rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, whether patients with SCD are at greater risk for serious COVID-19 illness including ICU admission, mechanical ventilation, and death is uncertain. Early in the pandemic, there were a number of published case series of patients with SCD and COVID-19 that revealed that most adult patients with SCD had mild to moderate disease courses [ [26] , [27] , [28] , [29] ]. And one study concluded that although patients with SCD and COVID-19 visited the emergency department and were hospitalized more frequently than the general population, that SCD status did not carry an added risk of COVID-19 related severe illness or death compared to a population with similar demographics and comorbidities [ 10 ].…”
Section: Clinical Presentations Of Covid-19 In Patients With Sickle C...mentioning
confidence: 99%
“…However, whether patients with SCD are at greater risk for serious COVID-19 illness including ICU admission, mechanical ventilation, and death is uncertain. Early in the pandemic, there were a number of published case series of patients with SCD and COVID-19 that revealed that most adult patients with SCD had mild to moderate disease courses [ [26] , [27] , [28] , [29] ]. And one study concluded that although patients with SCD and COVID-19 visited the emergency department and were hospitalized more frequently than the general population, that SCD status did not carry an added risk of COVID-19 related severe illness or death compared to a population with similar demographics and comorbidities [ 10 ].…”
Section: Clinical Presentations Of Covid-19 In Patients With Sickle C...mentioning
confidence: 99%